Pengaruh Budaya Organisasi, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan PT. XYZ - Damayanti, Mila Aisilia; Rizqi, Maulidyah Amalina; Saepuloh, Asep (Jurnal Mahasiswa Manajemen, 2024)
Background – The performance of employees of PT. XYZ can be measured through the completion of its tasks effectively and efficiently and being able to perform roles and functions that are in accordance with its work and all of it is positively related to the success of a company. The problems that occur in the company, namely poor employee organizational culture, lack of employee work motivation, and decreased employee work discipline are the causes of declining employee performance from the first to the fourth quarter. Objective – This study aims to examine the influence of organizational culture, work motivation, and work discipline on employee performance. Design / Methodology / Approach – The research utilized a saturated sample technique with the entire population of employees, consisting of 45 respondents. The study employed multiple linear regression analysis. Findings - The regression results indicate that organizational culture has a significant positive impact on employee performance. Work motivation also shows a significant positive influence on employee performance, as does work discipline. Limitations – The research is limited by geographical constraints due to the distant location of the research site and time constraints.